Peta Pendekatan Pendidikan Kristen: Tinjauan Teologis, Pedagogis, Psikologis - Obertina Gomor; Tirza Tanzania; Sarmauli Sarmauli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This article explores the map of Christian education approaches from theological, pedagogical, psychological, and contextual perspectives. Christian education plays a vital role in shaping the faith, character, and spirituality of students in a comprehensive manner. Using a literature review method, the study analyzes various sources on Christian education theology. The findings reveal that the theological approach emphasizes the Bible as the primary foundation for learning, while the pedagogical approach focuses on active and participatory teaching methods. The psychological approach tailors instruction to the developmental stages of students, and the contextual approach links faith with students' real-life experiences. Each approach has its strengths and limitations, and Christian educators are encouraged to integrate these approaches to achieve holistic learning goals. The study emphasizes the importance of collaboration among schools, families, and churches to create an educational ecosystem that fosters the spiritual and character growth of students. By combining these approaches, educators can better equip students for both spiritual and personal development.